HPV frequency, p16 expression and risk factors for oral leukoplakia from Córdoba, Argentina - Gerardo Gilligan (Asociación Colombiana de Infectología, 2023)
Background: Non-homogeneous results about the frequency of HPV in leukoplakia are presented in current literature, possibly linked to different factors. Among them, a diverse HPV geographical distribution was suggested. This study aimed to describe the frequency of HPV in patients diagnosed with leukoplakia. Patients & Methods: A cross-sectional study was carried out at the Facultad de Odontología, Universidad Nacional de Córdoba. HPV status was studied by polymerase-chain reaction (HPV-PCR) and p16 by immunohistochemistry. HPV status was analyzed concerning the clinical-demographic features using the Fisher test and the McNemar test. Results: There were included 33 patients diagnosed with different subtypes of oral leukoplakia. HPV genome was detected by PCR in 48.5% (n=16). The most com-mon viral genotype was HPV16. p16 was positive in 27% (n=9) of the cases. The concordance between HPV detection techniques showed poor or weak agreement (Mc Nemar 0.1185). Except for chronic mechanical irritation with HPV-PCR + (p=0.0049), and tongue location with HPV-PCR + (p=0.0366), no significant statistical association between the other included variables was found. Conclusions: The low frequency of HPV in this study agrees with previous studies of our region. Chronic mechanical irritation could play a role in the development of HPV-associated leukoplakias, mainly located on the ventrolateral tongue.